Pemetaan Kemampuan Awal Matematika Mahasiswa FKIP UPP berdasarkan Analisis Kesalahan Newman - Rika Septianingsih; Lutfiyah Ni’matuz Zakiyah (Kilau Publishing, 2026)
Mathematical prior knowledge is a crucial foundation for students’ success in learning mathematics at the tertiary level. This study aims to map the prior mathematical abilities of students in the Mathematics Education Study Program based on Newman Error Analysis (NEA) and to identify the dominant types of errors that occur across various basic mathematics topics. The research employed a descriptive quantitative method with 16 first-semester students as participants. The instrument used was a prior mathematics ability test covering social arithmetic, algebra, geometry, circles, trigonometry, functions, and calculus. Data analysis was conducted in two stages: descriptive quantitative analysis to determine students’ levels of achievement, and NEA-based error analysis to classify errors into five categories, namely reading errors, comprehension errors, transformation errors, process skills errors, and encoding errors. The results show that students’ average achievement varied across topics, with the highest performance in social arithmetic (95.83%) and the lowest in functions (53.13%). The dominant errors identified were transformation errors and process skills errors, particularly in algebra, geometry, trigonometry, and functions. These findings confirm that NEA is an effective diagnostic tool for identifying students’ cognitive barriers in mathematical problem solving and provides a basis for designing more adaptive and conceptually oriented instructional strategies.